Fungal Community Structure and As-Resistant Fungi in a Decommissioned Gold Mine Site - Crognale, Silvia; D'Annibale, Alessandro; Pesciaroli, Lorena; Stazi, Silvia R.; Petruccioli, Maurizio (Frontiers in Microbiology, 2017)
Although large quantities of heavy metal laden wastes are released in an uncontrolled manner by gold mining activities with ensuing contamination of the surrounding areas, there is scant information on the mycobiota of gold-mine sites. Thus, the present study was aimed to describe the fungal community structure in three differently As- and Hg-polluted soils collected from the Pestarena decommissioned site by using Illumina® metabarcoding. Fungal richness was found to increase as the contamination level increased while biodiversity was not related to the concentrations of inorganic toxicants. Within the phylum Zygomigota which, irrespective of the contamination level, was predominant in all the soils under study, the most abundant genera were Mucor and Mortierella. The relative abundances of Basidiomycota, instead, tended to raise as the contamination increased; within this phylum the most abundant genera were Cryptococcus and Pseudotomentella. The abundance of Ascomycota, ranging from about 8 to 21%, was not related to the contamination level. The relative abundances of those genera (i.e., Penicillium, Trichoderma and Chaetomium), the cultivable isolates of which exhibited significant As-resistance, were lower than the set threshold (0.5%). . Mass balances obtained from As-exposure experiments with these isolates showed that the main mechanisms involved in counteracting the toxicant were accumulation and, above all, volatilization, the respective extents of which ranged from 0.6 to 5.9% and from 6.4 to 31.2% in dependence of the isolate.